Efficacy and safety of acupuncture in the treatment of the sequela of olfactory disorders after infection with COVID-19: A protocol for systematic review and meta analysis. Issue 39 (30th September 2022) - Tang, Chao; He, Xiaoqin; Fu, Wenkang; Du, Yaxin; Huang, Yuxin; Liu, Lu; Lan, Wanning; Luo, Runjun; Liu, Yue
Abstract : Background: From the end of 2019 to now, coronavirus disease 2019 (COVID-19) has put enormous strain on the world's health systems. As a characteristic sign of COVID-19 patient, olfactory dysfunction (OD) poses considerable problems for patients. In China, acupuncture has been widely used to treat OD caused by COVID-19, but there is still a lack of evidence-based medical evaluation. This study was designed to evaluate the effectiveness and safety of acupuncture for the treatment of COVID-19 OD. Methods: According to the retrieval strategies, randomized controlled trials on the acupuncture for COVID-19 OD were obtained from Cochrane Central Register of Controlled Trials, Embase, PubMed, Web of Science, the Chinese National Knowledge Infrastructure, the Chinese Biomedical Literature Database, the Chinese Scientific Journal Database and the Wanfang Database, regardless of publication date, or language. Studies were screened based on inclusion and exclusion criteria, and the Cochrane risk bias assessment tool was used to evaluate the quality of the studies. The meta-analysis was performed using Review Manager (RevMan 5.3) and STATA 14.2 software. Ultimately, the evidentiary grade for the results will be evaluated. Results: The results of this meta-analysis will be submitted to a peer-reviewed journal for publication. Conclusion: This study will provide up-to-date summary proof for evaluating the effectiveness and safety of acupuncture for COVID-19 OD.